Correlation between clinicopathological indices and expression of cluster of differentiation 24 and cluster of differentiation 44 biomarkers in oral epithelial dysplasia and oral squamous cell carcinoma patients: A follow-up study - Narges Ghazi; Nasrollah Saghravanian; Kazem Anvari; Majid Mirhashemi; Mohammadhadi Erfanian (Wolters Kluwer Medknow Publications, 2024)
Background: Oral squamous cell carcinoma (OSCC) is the most common oral cavity cancer and may occur following oral epithelial dysplasia (OED). Cancer stem cells (CSCs) can self-renew and multi-directionally differentiate to promote tumorigenesis with high expression of cluster of differentiation (CD) 24 and CD44 markers. CSCs play a pivotal role in tumor development, drug resistance, and relapse after treatment. We aimed to evaluate the correlation between both marker expressions and clinicopathological indices in OED and OSCC patients. Materials and Methods: In this follow-up study, we could access 37 patients, including 12 OEDs and 25 OSCCs (Grade I: n = 9, Grade II: n = 8, and Grade III: n = 8). Data were analyzed using SPSS software (version 26) and log-rank tests, Fisher's exact test, Chi-square, and one-way ANOVA. P < 0.05 was considered statistically significant. Results: There was no significant difference in the expression of CD24 and CD44 markers between the study groups (P > 0.05) and the expression of both markers and clinicopathological indices in the study groups (P > 0.05). The mean and standard deviation of overall survival (OS) were 54.46 ± 43.08 with a range of 6-193 months, and they were 8.24 ± 15.34 months with a range of 0-70 months for disease-free survival (DFS) in patients, respectively. The average of DFS in Grade I was significantly lower than the OED (P = 0.002) and Grade II (P = 0.039) groups. The OS average in the Grade I (P = 0.014) and Grade III (P = 0.004) groups was statistically lower than the OED group. Conclusion: Although more than half of the patients demonstrated high expression of both markers, there was no statistically significant difference between them and clinicopathological indices.